1988
DOI: 10.1136/bmj.297.6663.1584
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium free dialysis for uraemic pruritus.

Abstract: potential for growth, presumably as a result of metabolic disturbances during the pregnancy, and may therefore be termed "macrosomic."Acker et al' reported that the incidence of shoulder dystocia in the deliveries of diabetic mothers was 50%, 23%, and 9% for infants weighing :4500 g, 4000-4499 g, and 3500-3999 g, respectively, compared with 23%, 10%, and 2% for deliveries of non-diabetic mothers. Thus many more infants of diabetic mothers are too large for their maternal pelvis, even when their birthweight is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…In contrast, Carmichael et al [29] failed to demonstrate a beneficial effect of reduction in magnesium on pruritus. In their trial, although they showed that a magnesium-free dialysis fluid corrected hypermagnesaemia, it failed to improve renal itch.…”
Section: Modification Of Dialysis Techniquesmentioning
confidence: 92%
“…In contrast, Carmichael et al [29] failed to demonstrate a beneficial effect of reduction in magnesium on pruritus. In their trial, although they showed that a magnesium-free dialysis fluid corrected hypermagnesaemia, it failed to improve renal itch.…”
Section: Modification Of Dialysis Techniquesmentioning
confidence: 92%
“…Hypervitaminosis A [6], hypermagne semia [5], and HPTH [4] have been indicated as possible responsible factors. All uremic patients have hypervitam inosis A, but not all of them suffer from pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…Pruritus can be exclusively intradialytic, but more often it is continuous with intradialytic exacerbation. Several etiopathogenetic hypotheses have been formu lated: hyperparathyroidism (HPTH) [4], hypermagne semia [5] and hypervitaminosis A [6], Studies on the biocompatibility of the components of dialytic circuits have suggested their possible role in the pathogenesis of dialytic intolerance phenomena [7][8][9][10][11]. Ethylene oxide (EO) in particular has been regarded as a major factor [12].…”
Section: Introductionmentioning
confidence: 99%
“…An increased skin divalent ion concentration may lead to microprecipitation of calcium or magnesium phosphate, which may be the cause of pruritus. In spite of these facts, only a few studies showed a significant correlation between serum or skin divalent ion content and the presence of pruritus [7,22,43,47]. Magnesium itself may be involved in the modulation of nerve conduction and release of histamine from mast cells [44].…”
Section: Divalent Ionsmentioning
confidence: 99%